Local-scale residential concentration and income inequalities of the main foreign-born population groups in the Spanish urban space. Reaffirming the model of a divided city. - Benassi, Federico; Iglesias-Pascual, Ricardo (Journal of Ethnic & Migration Studies, 2023)
This study presents a spatial analysis of suburban inequalities (residential concentration and income inequalities) among the main foreign-born population groups resident in Spain (Italians, Britons, Chinese, Moroccans and Romanians) in Madrid and Barcelona. Through a local spatial approach at census tract level, a number of relevant issues are highlighted, including the existence, both in Madrid and in Barcelona, of a divided space that shows a marked contrast between the city of the rich and that of the poor. The former includes the foreign-born population from more developed countries, while the latter contains Moroccans and Romanians. The Chinese population seem to follow their own pattern, which cannot be compared to that of the other population groups. It therefore seems that country of birth determines the outcome of spatial distributions and the degree of integration in spatially divided, and therefore more fragile, contexts. The emergent theme of divided cities, especially in its ethnic and spatial dimension, is gaining increased importance in 'old Europe'.